2022
DOI: 10.1109/lra.2022.3192885
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready for Radar to Replace Lidar in All-Weather Mapping and Localization?

Abstract: In this work, we demonstrate continuous-time radar-inertial and lidar-inertial odometry using a Gaussian process motion prior. Using a sparse prior, we demonstrate improved computational complexity during preintegration and interpolation. We use a white-noise-on-acceleration motion prior and treat the gyroscope as a direct measurement of the state while preintegrating accelerometer measurements to form relative velocity factors. Our odometry is implemented using slidingwindow batch trajectory estimation. To ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…3. Recent spinning radars without Doppler measurements have demonstrated high range, accuracy, and richness and have inspired numerous methods; from odometry estimation and alignment quality assessment to global localization [10], [14], [40]- [44], localization in previous maps [41] and SLAM [2], [15].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…3. Recent spinning radars without Doppler measurements have demonstrated high range, accuracy, and richness and have inspired numerous methods; from odometry estimation and alignment quality assessment to global localization [10], [14], [40]- [44], localization in previous maps [41] and SLAM [2], [15].…”
Section: Related Workmentioning
confidence: 99%
“…Burnett et al [9] presented a sliding window batch odometry estimation framework and found that a larger window up to at least 4 scans improved online odometry. Later, Burnett et al [10] used local submaps of radar detections aggregated from 3 scans within a teach and repeat localization framework [10]. Despite this, no systematic evaluation has been carried out to investigate the principled benefit of considering additional scans in spinning radar research.…”
Section: Aggregating Scans For Pose Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the conventional system the length is calculated by LiDAR 3D for obtaining the 3D bounding box, the proposed model’s 3D formation accuracy will be more accurate because of having an actual length received from the surveillance camera system. Moreover, researchers are working to replace LiDAR [ 61 ] with advanced RADAR systems as well as multi-sensed 3D camera imaging with AIP technologies because of some commercial use limitations of LiDAR such as its high expense, high signal interference and noise, and the problem of having rotating parts. “Will have or have not LiDAR”, the detection by surveillance camera systems, will be supportive for self-driving AVs in all conditions.…”
Section: Proposed Approaches For Detection Localization and Ai Networ...mentioning
confidence: 99%
“…Although better results are achieved with a fusion of radar and lidar. A more recent study by [5] extends the radar SLAM topic by comparing three localization systems: radar-only, lidaronly, and a cross-modal radar-to-lidar system across varying seasonal and weather conditions. their comparison shows that, with modern algorithms, lidar localization may not preform as poorly in bad weather as other studies have shown.…”
Section: Related Workmentioning
confidence: 99%